Calcining Temperatures of Sr1-3xEuxDy2xAl2O4 (x = 0−0.12) Phosphors Prepared Using the Potassium Carbonate Coprecipitation method - Liang, Chen-Jui; Siao, Hao-Yi (Journal of alloys and compounds, 2016)
This study investigated the optimal calcining temperatures of Sr1-3xEuxDy2xAl2O4 (x = 0−0.12) phosphors prepared by a new coprecipitation method using potassium carbonate as the precipitant. The results show that the potassium carbonate coprecipitation method was useful and successful, and avoids the problems of residual precipitant presence and the elution of small metal ions. The optimal calcining temperatures of the phosphors ranged from 920 to 950 °C, which were lower than those obtained using other methods. An empirical model was established to examine the calcining temperatures of prepared precursors. The average absolute relative error between the starting temperatures obtained from thermogravimetric analysis and temperatures estimated by the empirical model was 0.23%. The emission intensity increment rate of the phosphors produced using the potassium carbonate coprecipitation method between the doping amounts x of 0.01 and 0.06 is approximately 10-fold higher than that produced using the solid–state reaction method. Emission intensities of the prepared phosphors were increased approximately 23.5-fold when the doping amount was increased from 0.01 to 0.06. Sr0.64Eu0.12Dy0.24Al2O4 phosphor has moderate surface characteristics and the highest surface Dy/Eu ratio of all phosphors; therefore, its emission intensity is greater than those of other prepared phosphors. •Investigate optimal calcining temperatures to prepare high efficiency phosphors.•Our method reduces the energy required and operation time.•Offer many advantages such as high purity and high photoluminescence properties.•A prediction approach of the optimal calcining temperatures is introduced.